Protein Palmitoylation and Its Role in Bacterial and Viral Infections - Sobocińska, Justyna; Roszczenko-Jasińska, Paula; Ciesielska, Anna; Kwiatkowska, Katarzyna (Frontiers in Immunology, 2018)
S-palmitoylation is a reversible, enzymatic posttranslational modification of proteins in which palmitoyl chain is attached to a cysteine residue via a thioester linkage. S-palmitoylation determines the functioning of proteins by affecting their association with membranes, compartmentalization in membrane domains, trafficking and stability. In this review we focus on S-palmitoylation of proteins which are crucial for the interactions of pathogenic bacteria and viruses with the host. We discuss the role of palmitoylated proteins in the invasion of host cells by bacteria and viruses, and those involved in the host responses to the infection. We highlight recent data on protein S-palmitoylation in pathogens and their hosts obtained owing to the development of methods based on click chemistry and acyl-biotin exchange allowing proteomic analysis of protein lipidation. The role of the palmitoyl moiety present in bacterial lipopolysaccharide and lipoproteins, contributing to infectivity and affecting recognition of bacteria by innate immune receptors is also discussed.